Ayurvedic Management of Primary Dysmenorrhea with Abhayatrivrudadi Kashayam- Case Report (International Journal of Ayurveda and Pharma Research, 2022)
Dysmenorrhea, one of the most prevalent gynaecological problems in young women, particularly among teenagers, characterized by painful menstruation severe enough to prevent a person from doing day-to-day activities. It is the main factor behind young women's missed job and school days of teenagers. Primary dysmenorrhea is widely prevalent in more than 70% of teenagers and 30 -50% of menstruating women. Among Yonirogas, Udavarta yonivyapat is a condition characterized by painful menstruation and the relief of discomfort following blood discharge, which is typical of primary dysmenorrhea. In modern medical science, various forms of treatments are available for the relief of Primary dysmenorrhea which includes antispasmodic, analgesics, prostaglandin synthesis inhibitors, hormonal therapy etc. Reluctance of young girls and ladies to adopt the hormone therapies bring them to Ayurvedic treatment or any other alternative treatment of their choice. Ayurvedic management aims at vatanulomana through Snehana, Swedana, Vasti along with Samana oushadha which can alleviate Vata. Abhayatrivrudadi kashaya mentioned in the context of Udavarta chikitsa from Chikitsa manjari consists of Abhaya, Trivrut, Kulatha, Pippali and Eranda taila. Properties of this yoga include Vatanulomana, Sulaghna and Udavartahara. An 18 year old girl complained with severe pain during menstruation, low back ache, nausea and vomiting came to the OPD of Prasutitantra & Streeroga, Government Ayurveda College, Tripunithura is taken for this study. It is evident from the case study that Abhayatrivrudadi kashaya is effective in the management of primary dysmenorrhea.